2021
DOI: 10.1590/s1980-220x2020006603720
|View full text |Cite
|
Sign up to set email alerts
|

Women's satisfaction with childbirth and postpartum care and associated variables

Abstract: Objective: To determine the level of satisfaction with childbirth and the postpartum period. Method: This is a longitudinal, observational study. Clinical variables of the patients and delivery were collected, and a descriptive and inferential analysis was performed. The validated state-trait anxiety inventory (STAI) and the satisfaction survey Care in Obstetrics Measure For Testing Satisfaction Scale (COMFORTS) in Spanish were used. Results: A total of 381 women was included in the study and grouped into sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
7
0
5
Order By: Relevance
“…The analysis of the four dimensions of the COMFORTS scale showed that dimension 1, related to childbirth care, was the highest valued, while dimension 3, related to newborn care, was the lowest valued. Another study carried out in our country also found that this dimension was the lowest valued [ 29 ]. This analysis of the dimensions will allow us to focus our efforts to implement measures that allow us to improve the quality of care.…”
Section: Discussionmentioning
confidence: 79%
“…The analysis of the four dimensions of the COMFORTS scale showed that dimension 1, related to childbirth care, was the highest valued, while dimension 3, related to newborn care, was the lowest valued. Another study carried out in our country also found that this dimension was the lowest valued [ 29 ]. This analysis of the dimensions will allow us to focus our efforts to implement measures that allow us to improve the quality of care.…”
Section: Discussionmentioning
confidence: 79%
“…El autor (Navas et al, 2021) señala la satisfacción en la experiencia del parto se involucra diferentes factores; el tipo de parto es esencial en el momento de experimentar un buen grado de confort, es decir, tener un parto natural y permanecer más tiempo piel a piel en las primeras horas del recién nacido, por otro lado promover las buenas prácticas de atención del parto, así como identificar los niveles de estrés y de ansiedad durante el periodo de gestación, de esa manera la experiencia del parto será más agradable en la unidad hospitalaria (Carquillat et al, 2017) indica que los factores que contribuyen en una buena experiencia en la sala de parto varían según los tipos de parto, en el caso del parto por cesárea las gestantes se sintieron más preocupadas, una disminución de la confianza, es decir, que los primeros momentos del recién nacido son los menos vividos en comparación de las mujeres que dieron a luz por vía vaginal.…”
Section: Fundamentación Empírica De La Satisfacción De Las Mujeres En...unclassified
“…Más allá de la calidad de servicio que reciben las madres existen otros factores que influyen en la satisfacción, según el autor (Tiznobaik et al, 2019) el alivio del dolor durante el parto incide en la percepción de la madre, al igual que la comprensión del procedimiento del parto y el conocimiento del proceso así como la familiarización con el ambiente hospitalario, lo que genera un parto sin estrés De acuerdo a (Luzolo et al, 2020) la reducción del nivel de estrés de la madre en el proceso del parto mejora la experiencia y nivel de satisfacción. De igual forma (Navas et al, 2021) indica que el contacto inmediato piel a piel con el recién nacido alivia el estrés de la madre. Entre otros de los factores influyentes (Carquillat et al, 2017) resalta que estos dependerán también del tipo de parto ya sea por cesárea o parto vaginal, de la mismo modo (Daniele, 2021) añade la importancia del apoyo emocional que reciba la madre en el proceso, para que se halle satisfecha con su experiencia al dar a luz.…”
Section: Introductionunclassified
“…A literatura aponta variáveis que se relacionam com a satisfação do parto: acessibilidade, ambiente físico, limpeza, disponibilidade de medicamentos, suprimentos e recursos humanos, privacidade e confidencialidade, presteza, suporte emocional adequado, tipo de parto, contato pele a pele com o recém-nascido, apoio contínuo durante o processo, procedimentos executados e informações recebidas durante o trabalho de parto (6)(7) .…”
Section: Introductionunclassified